2015
DOI: 10.1080/19768354.2015.1042405
|View full text |Cite
|
Sign up to set email alerts
|

Fermented bitter gourd extract differentially regulates lipopolysaccharide-induced cytokine gene expression through nuclear factor-κB and interferon regulatory factor-1

Abstract: Bitter gourd is the fruit of a tropical vine in Asia, Africa, and South America where it is commonly used in traditional medicine. Our study tested the effects of a fermented extract of the bitter gourd on the inflammatory activities of the human monocytic leukemia cell line, THP-1. Treatment with the extract resulted in the suppression of phagocytic as well as lipopolysaccharide (LPS)-induced adhesion activity. Interestingly, the LPS-induced expression of matrix metalloproteinase-9 (MMP-9) and tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 111 , 112 , 113 Reports have shown bitter melon increased superoxide dismutase activity 114 and attenuated pro-inflammatory signaling in myocardial infarction, mitochondrial oxidation and HFD or other biological agents (ethanol, lipopolysaccharide, bacterial) induced neuroinflammation, and macrophage/mast cell infiltration in mice. 17 , 26 , 115 , 116 , 117 , 118 Briefly, our results show BMJ intervention has an expansive influence on immunity signaling as indicated by its targeting of innate/adaptive (GO 0045087, GO 0002460), humoral immune (GO 0006959) and general immune activation (GO 0002253) responses to combat pro-inflammatory mediators involved in adipocytokine signaling. Specifically, our study results showed that BMJ leads to inhibition of pro-inflammatory cytokine ( Ccl2 ), and higher levels of DG(40:1) (adipocytokine-associated metabolite).…”
Section: Discussionmentioning
confidence: 69%
“… 111 , 112 , 113 Reports have shown bitter melon increased superoxide dismutase activity 114 and attenuated pro-inflammatory signaling in myocardial infarction, mitochondrial oxidation and HFD or other biological agents (ethanol, lipopolysaccharide, bacterial) induced neuroinflammation, and macrophage/mast cell infiltration in mice. 17 , 26 , 115 , 116 , 117 , 118 Briefly, our results show BMJ intervention has an expansive influence on immunity signaling as indicated by its targeting of innate/adaptive (GO 0045087, GO 0002460), humoral immune (GO 0006959) and general immune activation (GO 0002253) responses to combat pro-inflammatory mediators involved in adipocytokine signaling. Specifically, our study results showed that BMJ leads to inhibition of pro-inflammatory cytokine ( Ccl2 ), and higher levels of DG(40:1) (adipocytokine-associated metabolite).…”
Section: Discussionmentioning
confidence: 69%
“…Cell culture media were composed of DMEM supplemented with 10% FBS, penicillin (100 U/mL), and streptomycin (100 μg/mL). To instigate an inflammatory state, bacterial LPS (100 ng/ml) was added to the media for 4 hrs (Jang et al 2015). siRNA RAW264.7 cells were plated into 100-mm-diameter dishes 18-24 h prior to transfection.…”
Section: Methodsmentioning
confidence: 99%